The negative health spillover effects of universal primary education policy: Ethnographic evidence from Uganda - Erin V. Moore; Jennifer S. Hirsch; Neema Nakyanjo; Rosette Nakubulwa; Bridget Morse-Karzen; Lee Daniel; Esther Spindler; Fred Nalugoda; John S. Santelli (Taylor & Francis Group, 2023)
Scholars of global health have embraced universal education as a structural intervention to prevent HIV. Yet the costs of school, including fees and other ancillary costs, create an economic burden for students and their families, indicating both the challenge of realising the potential of education for preventing HIV and the ways in which the desire for education may produce vulnerabilities to HIV for those struggling to afford it. To explore this paradox, this article draws from collaborative, team-based ethnographic research conducted from June to August 2019 in the Rakai district of Uganda. Respondents reported that education is the most significant cost burden faced by Ugandan families, sometimes amounting to as much as 66% of yearly household budgets per student. Respondents further understood paying for children's schooling as both a legal requirement and a valued social goal, and they pointed to men's labour migrations to high HIV-prevalence communities and women's participation in sex work as strategies to achieve that. Building from regional evidence showing young East African women participate in transactional, intergenerational sex to secure school fees for themselves, our findings point to the negative health spillover effects of Uganda's universal schooling policies for the whole family.